Performing Ultrasound-Guided Pharmacopuncture and Acupotomy for Nerve Entrapment in the Upper Extremity: A Guide for Teaching Procedural Skills - Taeseong Jeong; Eunbyul Cho; Sungha Kim; Seunghyun Oh; Suhak Kim; Jeongsu Park; Sungchul Kim (MEDrang Inc., 2024)
The use of ultrasound (US)-guided interventions has rapidly increased in Korean medicine (KM) to ensure the safety and accuracy of invasive procedures, such as pharmacopuncture and acupotomy. Although hands-on training is important for the acquisition of skills, it requires considerable time and cost. A detailed guide on the procedure and treatment regions is needed to ensure hygiene and safety during US-guided procedures in KM practice. In this study, we present the overall procedure, target structures, and treatment approaches of US-guided pharmacopuncture and acupotomy for nerve entrapment in the upper extremities of the cubital and radial tunnel, posterior interosseous nerve, carpal tunnel, and Guyon's canal syndrome. We believe that the findings of our study will serve as a foundation for future clinical research, practice, and education on US-guided KM procedures. Further research involving US-guided interventions should specify target structures in three-dimension to delineate the treatment areas.